Cost engineering : a practical method for sustainable profit generation in manufacturing - Domanski, Chris (Boca Raton : CRC Press, 2020)
"Cost Engineering provides a means for a manufacturer to achieve and sustain profitability by designing and manufacturing products to specific cost requirements. It incorporates a variety of proven methodologies including cost estimating, cost control, and cost optimization"--
OCLC-licensed vendor bibliographic record.
Keywords: Engineering economy; Product design; Cost effectiveness; Cost control; Profit; TECHNOLOGY / Manufacturing